The Potential of Using Quarry Dust as Sand Replacement Material in Production of Cement Sand Block - Wan, Shi Ying; Deraman, Rafikullah (Recent Trends in Civil Engineering and Built Environment, 2021)
Sand is an essential natural source that has been used commonly in the construction industry in Malaysia. With the rapid development of construction projects around the world, sand depletion had become a critical global issue arise in the world. The amount of sand decreasing while the price is increasing due to the high demand for this resource in construction projects. Quarry dust is one of the construction waste materials that will cause air pollution and increase the usage of the landfill if not managed properly. Thus, the purpose of this study is to examine the effect of quarry dust as partial sand replacement material in cement sand blocks production in terms of physical, mechanical, and thermal properties. The mix proportion of cement sand block used is 1(Cement):7(Sand) and the water-cement ratio is 0.6. The percentages used for quarry dust as sand replacement in the production of cement sand blocks vary from 0%, 5.0%. 10.0%, and 15.0%. A total of 60 units of solid cement sand blocks size of 400mm x 200mm x 100mm were produced. All the specimens were tested with sieve analysis, X-ray Diffraction (XRD), specific gravity, density, compressive strength, water absorption, and thermal conductivity. The result indicates that the optimum percentage of quarry dust as partial sand replacement block is at 15.0% as it showed the highest compressive strength value, 5.7 MPa >3.45MPa (ASTM C129-11), water absorption, 179 kg/m3 < 240 kg/m3 (ASTM C90-11a), density, 1973 kg/m3 in medium weight range of 1680-2000 kg/m3 (ASTM C129-11 for density), and thermal conductivity, 1.27 W/mK between range of 0.1 - 1.5 W/mK (BS 6073-2). These findings proved that quarry dust is a potential material that can be used as an alternative to sand in the production of cement sand blocks. As consequence using quarry dust can reduce the use of sand, reduce costs, and as well as reduce construction waste materials. Moreover, the use of quarry dust in the production of cement sand blocks can contribute to the production of environmentally friendly building materials that can create a sustainable built environment.